Experiencing Leadership: Connecting Theoretical Concepts and Practices of Leadership in Educational Contexts - Eftenaru, Cristina (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2024)
The purpose of this qualitative interpretive study was to identify aspects of leadership theory prevailing in the practice of educational leaders by analyzing how 22 participants experienced leadership. The study was framed using a conceptual framework grounded in a select body of theoretical and empirical leadership literature. Data were collected via interviews and were analyzed to identify themes within and across interviews. This study showed that leadership was perceived as a complex phenomenon and as responsibility rather than authority. In education, leadership occurred formally and informally, was highly contextual, and focused on students, teachers, and community. There were several interrelated processes that emerged in practice and impacted leadership and work environments: relationships, culture, decision-making, change, and risks. This study has value for leadership scholars, educators, and practitioners as it provides new insights on how educational leadership practices impact people and organizations.